β-Naphthoflavone, an exogenous ligand of aryl hydrocarbon receptor, disrupts zinc homeostasis in human hepatoma HepG2 cells - Takechi, Shinji; Ishida, Takumi (Journal of toxicological sciences, 2019)
Recent studies have demonstrated a relationship between the disruption of zinc homeostasis and the onset of diseases. However, little is known about the factors that disrupt zinc homeostasis. Here, we investigated the effects of β-naphthoflavone, an exogenous ligand of aryl hydrocarbon receptor (AHR), on intracellular zinc levels. Human hepatoma HepG2 cells were treated with β-naphthoflavone for 3 days, and intracellular labile and total zinc levels were assessed through flow cytometry and inductively coupled plasma atom emission spectroscopy, respectively. The mRNA levels of zinc transporters were determined by real-time PCR. Treatment of cells with β-naphthoflavone induced a decrease in intracellular labile zinc in a dose-dependent manner, with significantly decreased levels observed at 1 µM compared with controls. Additionally, intracellular total zinc levels demonstrated a decreasing trend with 10 µM β-naphthoflavone. Zinc pyrithione recovered the decrease in intracellular labile zinc levels induced by β-naphthoflavone, while zinc sulfate had no effect. Moreover, significant decreases in the mRNA levels of zinc transporters ZnT10 and ZIP5 were observed in response to 10 µM β-naphthoflavone. These results demonstrated that β-naphthoflavone has the potential to disrupt zinc homeostasis in hepatocytes. Although the underlying mechanism remains to be determined, suppression of zinc transporter transcription through AHR activation may be involved in the β-naphthoflavone-induced disruption of intracellular zinc levels.